2002
DOI: 10.1046/j.1365-2141.2002.03944.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adult systemic mastocytosis with interferon‐α: results of a multicentre phase II trial on 20 patients

Abstract: Summary. Systemic mastocytosis (SM) is characterized by proliferation of mast cells in various organs, which may release a wide variety of mediators, thereby explaining the broad clinical spectrum of disease manifestations. The potentially life-threatening systemic symptoms and tumoral proliferation are poorly controlled despite the use of several cytotoxic chemotherapies and/or symptomatic treatments. Twenty consecutive adult SM patients with histologically confirmed bone marrow (BM) involvement received inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 31 publications
2
96
0
1
Order By: Relevance
“…IFN may have some activity in ASM, with response rates varying between 12.5% in our study, to the 35% partial and 30% minor response rates reported by Casassus et al [26]. Understanding the disease biology may produce exciting novel targeted treatments.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…IFN may have some activity in ASM, with response rates varying between 12.5% in our study, to the 35% partial and 30% minor response rates reported by Casassus et al [26]. Understanding the disease biology may produce exciting novel targeted treatments.…”
Section: Discussionmentioning
confidence: 70%
“…Ex vivo studies revealed that IFN could exert inhibitory effects on factor-dependent growth of mast cells from circulating progenitor cells in patients with SM and a number of clinical reports have shown IFN to be useful in the treatment of ASM [3,[7][8][9][10][11][12][21][22][23][24][25]. In the largest series of patients reported, Casassus et al treated 20 consecutive adult SM patients with IFN 1-5 MU/m 2 /day SQ, with progressive dose intensification over the first month of treatment, to a maximum of 6 months [26]. Seven patients (35%) could not complete 6 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although IFN-alfa is probably the preferred drug for most patients in whom cytoreduction of the mast cell infiltrates is warranted, the side effects and required long duration can hamper application and continuation of this drug in many patients. 23 The report by Tefferi et al 14 advocating the use of cladribine seemed, therefore, an attractive alternative. We could, in a multicenter setting, confirm these results and observed an impressive positive effect of cladribine in all patients treated, although in none a definite complete remission was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments such as interferon-alpha with or without corticosteroids and cladribine exhibit low response rates that are usually partial in nature. [7][8][9] The D816V KIT mutation of SM has been shown to be resistant to the tyrosine kinase inhibitor imatinib mesylate (Gleevec) both in vitro and in vivo. [10][11][12] We therefore evaluated the effects of PKC412 (N-benzoyl-staurosporine, Novartis, Basel Switzerland), an alternative small molecule inhibitor of multiple type III receptor tyrosine kinases, including the KIT tyrosine kinase, in a patient with mast cell leukemia.…”
Section: Introductionmentioning
confidence: 99%